Development of thermal insulation from oil palm fiber for chimney of fire tube steam packaged boiler - Hassan, S. (Science and Engineering Institute, 2014)
In this study, an investigation was conducted to develop oil palm fiber from palm oil mill waste as a thermal insulator. The experimental study focused on comparisons of thermal conductivity and temperature gradient or difference between the existing commercial rockwool and the produced oil palm fiber as a thermal insulator for a chimney of steam packaged boiler. The experiments were conducted at different temperature ranges and packing density. The values of the measured thermal conductivity were found to be 0.02 W/mÂ¡?K to 0.112 W/mÂ¡? for a packing density of 78, 96 and 112 kg/m3 , and at a temperatures between 40 ?not;C to 90 ?C. The value of the thermal conductivity of the oil palm fiber showed an increase at higher temperatures and greater temperature gradient as compared to the rockwool insulator. Although not being able to match the values at higher temperatures and temperature difference, other factors such as the cost and the environmental benefits of using oil palm waste material should be taken into consideration and hence encouraging its use as at least a supplement to existing insulation materials.